2006
DOI: 10.1021/ic0519281
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of Primary and Secondary Phosphine Ligation on Ruthenium(II) Complexes

Abstract: Ruthenium(II) complexes of the primary phosphines PH2Fc and PH2CH2Fc and the secondary phosphine PH(CH2Fc)2, including [(p-cymene)RuCl(L)2](PF6) (p-cymene = p-iPrC6H4Me, L = PH2CH2Fc and PH(CH2Fc)2, 2b and 2c, respectively) and trans-[RuCl2(L)4] (L = PH2Fc, PH2CH2Fc, and PH(CH2Fc)2, 3a-c, respectively) were prepared and characterized by IR, 1H NMR, and 31P NMR spectroscopy. 3b was additionally characterized by X-ray crystallography. The spectroscopic effects of phosphine ligation were determined. Characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…4 We have previously extended this chemistry to the sterically demanding air-stable secondary and tertiary ferrocenylphosphines PH(CH 2 Fc) 2 and P(CH 2 Fc) 3 14 and transition metal complexes thereof. 14,[15][16][17][18][19] FcPH 2 is a remarkably convenient starting material considering its easy synthesis and stability compared with related compounds, but has mostly been neglected. In contrast, the highly reactive PhPH 2 has been used extensively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 We have previously extended this chemistry to the sterically demanding air-stable secondary and tertiary ferrocenylphosphines PH(CH 2 Fc) 2 and P(CH 2 Fc) 3 14 and transition metal complexes thereof. 14,[15][16][17][18][19] FcPH 2 is a remarkably convenient starting material considering its easy synthesis and stability compared with related compounds, but has mostly been neglected. In contrast, the highly reactive PhPH 2 has been used extensively.…”
Section: Introductionmentioning
confidence: 99%
“…20 We have previously reported the synthesis of [MI 2 (CO) 3 (PH 2 Fc) 2 ] (M = Mo, W), 19 [Cp*TaCl 4 (PH 2 Fc)] 15 (Cp* = C 5 Me 5 ) and [RuCl 2 ( pcymene)(PH 2 Fc)]. 17 Presented below is the synthesis and characterisation of the ferrocenylphosphine transition metal carbonyl complexes [M(CO) 5…”
Section: Introductionmentioning
confidence: 99%
“…The distances for the Ru-Cl (2.4275(9) A ˚) and Ru-P (2.3088(7) A ˚) bonds are comparable to those found in the literature. 7,8 The Ru, P and Cl atoms were located and refined anisotropically. The hydrogen atoms of the PH 3 groups were disordered due to rotation of the phosphine ligand about the Ru-P axis.…”
mentioning
confidence: 99%
“…We have already shown that the phosphines PH 2 Fc, PH 2 CH 2 Fc, and PH(CH 2 Fc) 2 (=L) react with transition metal complexes with reactive M-X bonds (X = halide) without loss of HX but with clean formation of the corresponding phosphine complexes, such as [Cp R TaCl 4 (L)] (Cp R = C 5 H 4 Me, C 5 Me 5 ) [12], [(p-cymene)RuCl 2 (L)] [3,13], [(p-cymene)Ru(Cl)(L) 2 ](PF 6 ) [14], trans-[Ru(Cl) 2 (L) 4 ] [14], [MI 2 (CO) 3 (L) 2 ] and [MI 2 (CO) 2 (L) 3 ] (M = Mo, W) [15][16][17]. The unexpected formation of the unique complex salt [WI(CO) 2 (PH 2 CH 2 Fc) 4 ]I is another example of the unusual coordinating properties of these phosphines [18].…”
Section: -(Ch 2 Oh)][wi 3 (Co) 4 ] (6) and [Ph(ch 2 Fc) 3 ][Wi 3 (Co)mentioning
confidence: 99%